Anxiety during alcohol withdrawal involves 5-HT2C receptors and M-channels in the lateral habenula. (February 2020) - Fu, Rao; Mei, Qinghua; Shiwalkar, Nimisha; Zuo, Wanhong; Zhang, Haifeng; Gregor, Danielle; Patel, Shivani; Ye, Jiang-Hong
Abstract: Anxiety disorders often co-occur with alcohol use disorders, but the mechanisms underlying this comorbidity remain elusive. Previously, we reported that rats withdrawn from chronic alcohol consumption (Post-EtOH rats) exhibited robust anxiety-like behaviors (AB), which were accompanied by neuronal hyperexcitability, and the downregulation of M-type potassium channels (M-channels) in the lateral habenula (LHb); and that serotonin (5-HT) stimulated LHb neurons via type 2C receptors (5-HT2C Rs). Also, 5-HT2C R activation is known to inhibit M-current in mouse hypothalamic neurons. The present study investigated whether LHb 5-HT2C Rs and M-channels contribute to AB in adult male Long-Evans rats. We used the intermittent-access to 20% ethanol two-bottle free-choice drinking paradigm to induce dependence. We measured AB with the elevated plus-maze, open-field, and marble-burying tests at 24 h withdrawal. We found that intra-LHb infusion of SB242084, a selective 5-HT2C R antagonist alleviated AB and reduced the elevated c-Fos expression in the LHb of Post-EtOH rats. By contrast, intra-LHb infusion of the selective 5-HT2C R agonist WAY161503 induced AB and increased c-Fos expression in the LHb in alcohol-naive but not Post-EtOH rats. Also, intra-LHb SB242084 significantly reduced self-administration of alcohol intake in the operant chambers. Furthermore, both 5-HT2C R protein levels and 5-HIAA/5-HT ratio was increased in the LHb of Post-EtOH rats. Finally, intra-LHb SB242084 increased LHb KCNQ2/3 membrane protein expression in Post-EtOH rats. Collectively, these results suggest that enhanced LHb 5-HT2C R signaling that interacted with M-channels triggers AB in Post-EtOH rats and that 5-HT2C Rs may be a promising target for treating comorbid anxiety disorders in alcoholics. Highlights: Blockade of LHb 5-HT2C R reduced anxiety-like behaviors (AB) and LHb Fos expression. Blockade of LHb 5-HT2C R reduced alcohol self-administration in the operant chamber. 5-HT2C R protein level was increased in the LHb of alcohol-withdrawn rats. The 5-HIAA/5-HT ratio was increased in the LHb of alcohol-withdrawn rats. AB involved enhancement of 5-HT2C R signaling and inhibition of M-channel in the LHb.